Inflation in Peru as a response to international energy and food prices shocks - Espinoza Ipanaque, Paul Christian (2023)
Objective: To determine the contribution of international energy and food price shocks in Peru’s inflation during the period 2002-2022. Method: A structural autoregressive vector model (SVAR) was estimated following the reflection of Blanchard and Quah so that it reflected the behavior of a small and open economy such as Peru's. In addition, the Granger causality test, cumulative impulse-response functions, and variance decomposition were used to achieve the goal. Results: The oil, grain and fertilizer price shocks are weakly inflationary, while the ocean freight shocks are weakly deflationary. In addition, these shocks explain slightly the need for inflation. Conclusion: In the long term, the contribution of international energy and food price shocks on domestic inflammation has been significant and permanent; however, the effects are weak and heterogeneous. This would be associated with good management of monetary policy by the Central Reserve Bank of Peru.